Flight dynamics - Stengel, Robert F. (Princeton University Press, 2004)
Flight Dynamics takes a new approach to the science and mathematics of aircraft flight, unifying principles of aeronautics with contemporary systems analysis. While presenting traditional material that is critical to understanding aircraft motions, it does so in the context of modern computational tools and multivariable methods. Robert Stengel devotes particular attention to models and techniques that are appropriate for analysis, simulation, evaluation of flying qualities, and control system design. He establishes bridges to classical analysis and results, and explores new territory that w.